"I've got you under my skin": Relational therapists' experiences of patients who occupy their inner world. Issue 2 (3rd April 2018) - Bimont, Diane; Werbart, Andrzej
Abstract : The aim of this study was to conduct an in-depth exploration of therapists' experiences of patients who affect them more than others and occupy their inner world beyond the context of therapy sessions. A phenomenological analysis was performed on semi-structured interviews with five relational therapists. All the therapists had a strong experience of a particular patient getting "under their skin." In all these cases, the patient was a traumatized woman. The distinctive characteristic of the phenomenon was a sense of blurred or too permeable boundaries between the therapist and the patient. This was associated with fear and anxiety, but also with feelings of love. The therapists' reactions to having a patient "under their skin" varied from resistance to symbiotic relatedness. The therapists' ideas of their professional role influenced how the experience of carrying the patient's suffering was interpreted. The phenomenon of the patient's presence in the therapist's representational world might be interpreted as a distinct countertransference phenomenon when working in a more "thin boundary" manner with particular cases. The therapists' ability to effectively manage their vulnerabilities, activated in the countertransference, seems to be crucial for therapeutic progress. Implications for research, clinical practice, and training are discussed.